Pengaruh Kepemimpinan Transformational terhadap Kinerja Karyawan: Systematic Literatur Review (Jurnal Manajemen Bisnis Digital Terkini, 2026)
Transformational leadership has a strong and positive impact on employee performance across various organizational sectors. This leadership style, which is based on four main dimensions—Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration plays a very important role in creating a shared vision, driving high internal motivation, and producing positive change. Research shows that this positive influence is often affected by factors such as commitment to the organization, job involvement, and organizational behavior. By encouraging employees to put aside personal interests to achieve collective goals, transformational leaders enhance effectiveness, productivity, and the quality of work outcomes. Bass's theory (1985) states that this leadership style drives performance beyond normal expectations. The conclusion of this study emphasizes that the application of transformational leadership style is crucial for organizational management in efforts to improve the quality of human resources. Companies are advised to conduct leadership training that focuses on developing emotional intelligence and visionary communication skills for managers.